Local and remote lesions in horses subjected to small colon distension and decompression - Faleiros, Rafael R.; Macoris, Delphim G. [UNESP]; Alves, Geraldo Eleno S.; Souza, Danielle G.; Teixeira, Mauro M.; Moore, Rustin M. [UNESP] (Canadian Vet Med Assoc, 2008)
The purpose of this study was to observe and characterize colonic and lung lesions in horses subjected to experimental distension and decompression of the small colon. Sixteen healthy adult horses were divided into 2 groups: 9 horses that were subjected to distension of the small colon by means of a latex balloon surgically implanted in the lumen and inflated to a pressure of 40 mm Hg for 4 h, and 7 horses in which the balloon was implanted but not inflated. Colonic biopsy specimens were collected before balloon implantation, at the end of the period of obstruction, and 1.5 and 12 h after decompression and were examined for hemorrhage, edema, and neutrophil infiltration; myeloperoxidase (MPO) activity and hemoglobin concentration were measured as well. At the end of the experiment, lung samples were also collected and examined for neutrophil accumulation and MPO activity. The mucosa was not affected by luminal distension; lesions were restricted to the seromuscular layer. Neutrophil accumulation and edema were observed in the samples from both groups of horses but were greater in those from the distension group, in which there was also hemorrhage, fibrin deposition, and increased MPO activity in the seromuscular layer. Similarly, there was greater accumulation of neutrophils in the lung samples from the distension group than in those from the sham-operated group, as determined by histologic evaluation and MPO assay. These findings provide new evidence of reperfusion injury and a systemic inflammatory response, followed by remote lesions, in horses with intestinal obstruction.